Further isotopic evidence for seaweed-eating sheep from Neolithic Orkney. (February 2017) - Schulting, Rick J.; Vaiglova, Petra; Crozier, Rebecca; Reimer, Paula J.
Abstract: The antiquity of the practice of grazing on and/or foddering with seaweed is of interest in terms of understanding animal management practices in northwest Europe, where provision had to be made for overwintering. Orkney holds a special place in this discussion, since the sheep of North Ronaldsay have been confined to the seashores since the early nineteenth century, and are entirely adapted to a diet consisting mainly of seaweeds. Here, we report the results of stable carbon and nitrogen isotope analysis of twenty-five faunal specimens from the Neolithic chambered tomb of Quanterness, Orkney. Three of the 12 sheep analysed show elevated δ 13 C values that can only be explained by the consumption of seaweed. Radiocarbon dates place two of the three animals in the Neolithic, coeval with the use of the monument for burial, while the third animal dates to the Chalcolithic/Early Bronze Age. The findings are placed into the wider context of previous isotopic analyses of domestic fauna from prehistoric Orkney. A possible disjoint is noted between the results for bone collagen – where seaweed consumption seems to relate to the pre-natal period, since all the animals with high δ 13 C values are less than ca. three months of age – and previous studies using high-resolution sequential enamel measurements, which suggest a repeated pattern of winter consumption of seaweed in older animals. Graphical abstract: Highlights: Three lambs from Quanterness, Orkney, exhibit high carbon & nitrogen isotope values. The lambs date to the Middle/Late Neolithic and to the Early Bronze Age. Seaweed consumption by ewes in the months prior to giving birth is likely. Evidence for seaweed consumption by sheep is patchy both spatially & temporally. A more integrated approach is needed to investigate the use of seaweed in prehistory.